Analisis Pengendalian Kualitas Produk SIR 3L di PT Perkebunan Nusantara VII Unit Usaha Way Berulu - Laras Fitriyani; Fitriani Fitriani; Rachmad Edison (Jurnal Agro Industri Perkebunan, 2016)
Rubber comes from rubber tree (Hevea brasiliensis Muell. Arg.) which is produced by major plantation and small plantation. Rubber as industrial material requires good quality assurance, so the company will try to do intensif quality control to the product material component, production process or final process. The implementation of the quality control relates to quality standard which is determined by the company. Quality control tries to minimize damage product, maintain to the final product fit to quality standard of certain company and avoid damage product comes to consument. This research is intended to identify production process of rubber crumb, analyse quality control of rubber crumb and find out factors affect the quality of SIR 3L at PTPN VII Way Berulu Business Unit. According to the result of the P-Chart Analysis, on January 2015 there are some product damages, but the damage can still be controled statistically. Proportion or average of the product damage is 0,063 and the highest damage appearef in 28 January with the presentage of 14,76. Main factor that cause the product damage is color index of rubber crumb which is more than scale 6 of lovibond comparator standard.Keywords: colour, crumb rubber, quality controlÂ Permalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/52